Outcomes for Implemented Macroeconomic Policy Responses and Multilateral Collaboration Strategies for Economic Recovery After a Crisis: A Rapid Scoping Review. (July 2021) - Embrett, Mark; Bielska, Iwona A.; Manis, Derek R.; Cooper, Rhiannon; Agarwal, Gina; Nartowski, Robert; Moore, Emily; Lopatina, Elena; Conway, Aislinn; Clark, Kathryn
To promote postpandemic recovery, many countries have adopted economic packages that include fiscal, monetary, and financial policy measures; however, the effects of these policies may not be known for several years or more. There is an opportunity for decision makers to learn from past policies that facilitated recovery from other disease outbreaks, crises, and natural disasters that have had a devastating effect on economies around the world. To support the development of the United Nations Research Roadmap for COVID-19 Recovery, this review examined and synthesized peer-reviewed studies and gray literature that focused on macroeconomic policy responses and multilateral coalition strategies from past pandemics and crises to provide a map of the existing evidence. We conducted a systematic search of academic and gray literature databases. After screening, we found 22 records that were eligible for this review. The evidence found demonstrates that macroeconomic and multilateral coalition strategies have various impacts on a diverse set of countries and populations. Although the studies were heterogeneous in nature, most did find positive results for macroeconomic intervention policies that addressed investments to strengthen health and social protection systems, specifically cash and unconventional/nonstandard monetary measures, in-kind transfers, social security financing, and measures geared toward certain population groups.